Supporting the sustainability agenda in healthcare. Issue 5 (October 2022) - Syed, Habib; Syed, Labib; Stone, Andrew; Phadnis, Joideep
Abstract: Sustainability in healthcare has gained major traction over the past decade, with clinicians, politicians and other key healthcare stakeholders recognizing the damaging effects that current practices are having on planetary health. Efforts have been made in research and innovation to raise widespread awareness and to formulate strategies by which healthcare services can help minimize and counteract the effects of climate change. The NHS in the UK has demonstrated the strength of its intent to help manage this evolving public health crisis through its pledge to become the first net-zero carbon health service by 2040. Surgical specialties, including orthopaedics, are a major contributor towards the production of greenhouse gas emissions within healthcare and therefore serve as a focal point for change in favour of environmental sustainability. Great progress has been achieved in recent years by incorporating greener practices into the provision of healthcare in the UK and worldwide. However, further change is still required, and at an accelerated pace if we are to mitigate the effects of climate change before irreversible damage occurs. Collaboration, leadership and a shared vision for change is essential in achieving true environmental sustainability in healthcare.